PELATIHAN PENYUSUNAN KEGIATAN PEMBELAJARAN BERBASIS LITERASI SEBAGAI IMPLEMENTASI KURIKULUM MERDEKA PADA GURU PAUD DI KECAMATAN PRIGEN - Melia Widayanti; Dewi Komalasari; Ruqoyyah Fitri (Program Studi S1, S2, S3 Mananajemen Pendidikan Universitas Negeri Surabaya, 2023)
The use of the concept of independent learning in education provides great potential for the development of better education in Indonesia. The condition of Kindergartens in Prigen District is that only a few plan and implement literacy-based learning. So there needs to be a conscious effort to encourage and train PAUD teachers in Prigen District to be able to have the knowledge and skills in planning literacy-based learning as part of the implementation of independent learning. This community service activity is in the form of literacy-based learning preparation training as an implementation of the independent learning curriculum for kindergarten tutors in Prigen District. This training uses discussion, lecture and simulation methods. The data collection technique used is Engineering. The result obtained is that the teacher's ability to design literacy-based learning increases, as evidenced by the increase in pre-test to post-test scores.